Glomus Tumor of the Cheek: A Case Report. (2nd July 2012) - Veros, Konstantinos; Markou, Konstantinos; Filitatzi, Chrysa; Kyrmizakis, Dionysios E.
Abstract : Glomus tumors are benign, subcutaneous neoplasms of the perivasculature. Though facial location is rare, the diagnosis of a glomus tumor should be considered in cases of undiagnosed painful facial nodules or chronic facial pain. Imaging aids in defining the tumor and planning a complete excision in order to avoid recurrence. Histological examination is mandatory after every attempted excision. A case of glomus tumor of the cheek along with the possible pitfalls of diagnosis and treatment and a brief review of the limited associated literature are presented.